Discurso de ódio LGBTI+fóbico e criminologia crítica no estudo dos danos sociais: um enfoque jurídico a partir da narrativa de vítimas na cidade de Santa Maria/RS - Mello, Pablo Domingues de (2023)
This work is part of the field of critical criminology, especially from the perspective of social harm. It also draws on the epistemological rupture of queer criminology, feminist criminologies, Afrocentered criminologies, and critiques of coloniality. With the base theory settled, the general objective of the study is to investigate, from the perspective of social harm, the limits and possibilities to propose a critical criminological construction of LGBTI+phobic hate speech propagated inside and outside the internet. The research is qualitative and adopts intersectional perspectives, epistemologically situated and departed from the methodological tools of Grounded Theory, with a constructivist basis as outlined by Kathy Charmaz. The following research problem was answered: what are the limits and possibilities for proposing a critical criminological analysis of LGBTI+phobic hate speech, practiced on the internet and beyond, that provides an adequate response to the pain of people who directly and indirectly live this experience? The empirical execution of the study had the direct participation of 108 (one hundred and eight) LGBTI+ individuals, victims of hate speech, over 18 (eighteen) years old, whose violence occurred in Santa Maria/RS or nearby region within a maximum radius of 200km, and had its execution approved by the Ethics Committee in Research with Human Beings (CEP) of the UFSM. The first stage of the research was through the application of an electronic questionnaire on the Google Forms platform. In the second stage, a semi-structured interview was applied to the first 10 (ten) volunteers who showed interest, through the electronic questionnaire, in participating in the interviews. It was concluded that LGBTI+ hate speech, direct and indirect, is present in the lives of LGBTI+ individuals in different spaces, from family to work and academic environments. A lack of interest and fear in denouncing this violence to state and private authorities was perceived, given the distrust of the victims towards this institution and its agents. The following damages were found: patrimonial damage; psychological damage subdivided into affective, emotional and family damage; loss of identification as a victim, subdivided into denial of victimhood and denial of violence; suicide in life, subdivided into feeling of loss of life, and cyber damage. The identified damages were perceived as consequences of violence derived from the cisheteronormative social structure. Hate speech is one of the forms of violence that ideologically legitimizes this structure, manifesting it, producing individual damages that, because they share a common basis with the social structure, are identified as social damages. Proposals were presented for the accountability of the aggressors and reparation for the victims, taken from the victims' firstperson statements and which pointed to Restorative and Transformative Justice, both from an intersectional and penal abolitionist perspective, as necessary paths.